THU0116 Biological Effects of the JAK1 Selective Inhibitor GLPG0634 on Inflammation Markers in Arthritic Mice. (23rd January 2014) - Vayssiere, B.; de Vos, S.; Merciris, D.; Auberval, M.; Dupont, S.; Vandeghinste, N.; Lepescheux, L.; Clement-Lacroix, P.; Delerive, P.; van Rompaey, L.; Brys, R.; Galien, R.
Abstract : Background: Non-selective Janus kinase (JAK) inhibitors have shown long-term efficacy in treating rheumatoid arthritis (RA). However, tolerated doses and thereby efficacy are limited due to JAK2-driven side effects. Selective inhibition of JAK1 may be associated with an improved safety profile while maintaining clinical efficacy. Currently available information for JAK1 inhibitors is limited. GLPG0634 is a JAK inhibitor which displays a high selectivity for JAK1 over JAK2 in human whole blood assays. It is currently being developed for RA treatment and displayed good efficacy and tolerability in a 4-week Phase 2a study. Objectives: Characterize the mode of action of a JAK1-selective inhibitor by measuring the impact of GLPG0634 on JAK pathway activity and inflammation parameters in blood and paws in the mouse CIA model. Methods: Mice with established collagen-induced arthritis (CIA) were treated with GLPG0634 (50 mg/kg po, bid) or etanercept (10 mg/kg ip, 3 times a week). Disease progression was evaluated using clinical score and histological parameters. Expression of genes related to JAK pathways and markers of inflammation were measured in hind paws as well as in circulating leukocytes (WBC) using qRT-PCR. Luminex technology was used to measure a panel of 35 cytokines and chemokines in mouse serum. Results: Oral treatment with GLPG0634 decreased inflammation in CIA in mice as measured by clinical scores and paw histology, with the same efficacy as etanercept. In paws of arthritic mice, an increase of 20- to more than 200-fold in the expression of inflammation markers (IL-6, IL-1β, TNFα, CXCL1) was found. A 30% to 45% decrease of their expression was observed in GLPG0634-treated arthritic mice. A similar expression pattern was observed for the osteoclast differentiation factor RANKL and for proteases linked to inflammation (MMP3, MMP13). These findings corroborate the bone and cartilage protective effects of GLPG0634 observed by histological analysis of paws. In addition, decreases from 30 to 70% in serum levels of cytokines and chemokines (IL-6, IP-10/CXCL10, MCP-1) in GLPG0634-treated arthritic mice confirmed the immunomodulation and anti-inflammatory effects. Of interest, the increased expression of JAK1-induced genes Mx1 and Mx2 in arthritic mice both in WBC and hind paws was abolished after treatment of animals with GLPG0634, whereas expression of the JAK2-dependent gene HRH4 was not altered by GLPG0634 treatment. These findings show that the decrease in inflammation markers was associated with inhibition of JAK1 but not JAK2. Conclusions: These data show that oral GLPG0634 administration reduces inflammation in the mouse CIA model to the same extent as parenteral etanercept. Effects on several inflammation markers in paws and serum demonstrate the anti-inflammatory activity of GLPG0634. These effects were achieved through selective JAK1 inhibition. These data establish that selective JAK1 inhibition by GLPG0634 is sufficient to mediate strong efficacy in an established arthritis model and provide some useful potential markers to follow pathology progression in arthritic mice and humans. Disclosure of Interest: B. Vayssiere Employee of: Galapagos SASU, S. de Vos Employee of: Galapagos NV, D. Merciris Employee of: Galapagos SASU, M. Auberval Employee of: Galapagos SASU, S. Dupont Employee of: Galapagos SASU, N. Vandeghinste Employee of: Galapagos NV, L. Lepescheux Employee of: Galapagos SASU, P. Clement-Lacroix Employee of: Galapagos SASU, P. Delerive Employee of: Galapagos SASU, L. van Rompaey Employee of: Galapagos NV, R. Brys Employee of: Galapagos NV, R. Galien Employee of: Galapagos SASU